Tinjaun terhadap Food Waste berdasarkan Teori Bioregionalisme Richard Evanoff dan Segitiga Steiner-Evanoff-UKDW - Pascalin Dwi Aprilia (Sekolah Tinggi Teologi Jaffray Jakarta, 2022)
Consumptive behavior is often only based on desires, not based on needs. One form of excessive consumptive behavior is throwing away food which then causes leftovers. This article focuses on consumptive behavior in the form of food waste that occurs in Indonesia and causes ecological damage and inequality in food consumption. This study aims to provide an overview of the importance of awareness of food waste which is studied using Richard Evanoff's bioregionalism theory and the Steiner-Evanoff-UKDW Triangle. The method used in this study is a qualitative method. The author will make a dialectic between the data obtained from the problems he is struggling with and sources of knowledge in the form of literature in the form of journals and websites. Based on the research it was found that cases of food waste and hunger in Indonesia must be overcome in order to achieve ecological sustainability, social justice, and human welfare. The church also has a role in mitigating and tackling the problem of food waste and in order to help other humans who also experience a shortage of food that is suitable for consumption so that God's grace is always maintained and voiced.